CONSTRAINTS ON THE COOLING RATES OF CHONDRULES FROM THE MICROSTRUCTURE OF CLINOPYROXENE AND PLAGIOCLASE - Weinbruch S.; Müller W.F. (My University, 1995)
Attempts are made to quantify cooling rates of chondrules from the microstructure of clinopyroxene and Ca-rich plagioclase. Pigeonite/diopside exsolution lamellae on (001) are frequently observed in Allende granular olivine pyroxene chondrules. Cooling rates of 2–10°C/h are obtained for the observed wavelengths between 25 and 33 nm from isothermal time-temperature-transformation diagrams. Modelling of lamellae growth during cooling yields similar cooling rates between 7 and 25°C/h. Coarsening of pigeonite/diopside exsolution lamellae takes place in the small temperature interval from approximately 1350 to 1200°C. The occurrence of type b-antiphase domains in Ca-rich plagioclase provides independent constraints on chondrule cooling rates. Isothermal time-temperature-transformation diagrams yield cooling rates of approximately 3–30°C/h for the observed domain sizes between 10 and 30 nm. Cooling rates derived from antiphase domains in plagioclase are valid in approximately the same temperature range than those deduced from pigeonite/diopside exsolution lamellae. Our estimates must be regarded as upper limits, and they seem to be significantly lower than those derived from dynamic crystallization experiments (100–2000·gC/h). As dynamic crystallization experiments yield cooling rates at higher temperatures near the liquidus, this observation may suggest nonlinear cooling. The absence of orthoenstatite lamellae in clinoenstatite indicates high cooling rates on the order of 104°C/h at temperatures around 1000°C.